Legitimação das universidades federais: análise dos enquadramentos construídos pelo jornal Zero Hora - Lenhardt, Wagner Guilherme (2021)
This dissertation has as its theme the legitimation strategies printed in the journalistic frameworks of Brazilian Federal Universities (UFs). We assume that the media participates in processes of (de) legitimization of institutions, such as public universities. Often, UFs have their existence threatened, mainly due to the budget cuts they suffer from the different governments that pass through Brazil. At the same time that journalism draws attention to this theme, several questions arise about UFs, generating tensions and divergent movements. As an empirical object, we will analyze the newspaper Zero Hora. Our time frame comprises the first and third semesters of Jair Bolsonaro's government, thus bringing together the first moments of a new political perspective for UFs and also the first months of the covid-19 pandemic, when scientific institutions had great visibility in the actions to fight the disease. The guiding question of this study is “what are the frameworks built by the newspaper Zero Hora in scheduling Federal Universities during the first semester of the Bolsonaro government and during the first semester of the new coronavirus pandemic in Brazil?”. As a general objective, we propose to analyze the frameworks built by the newspaper Zero Hora that operate in the (de) legitimation of UFs, considering the first six months of the Jair Bolsonaro government and the first six months of the new coronavirus pandemic in Brazil. Our theoretical framework, first, seeks to verify the role of UFs from the triad teaching, research and extension, based on authors in the field of Education (WANDERLEY, 2003; MARTINS, 2008; RAYS; 2003). Then, we used the notion of political field, journalistic field and scientific field to verify the crossings that occur between such spheres (BOURDIEU, 1989; COOK, 2011; RODRIGUES, 1990). We also articulate the concepts of strategies, legitimacy, legitimation and journalistic discourse (BOURDIEU, 2004; RODRIGUES, 1990; SODRÉ, 2006; BARICHELLO, 2018). As a theoretical-methodological proposal, we will use the framework studies (GAMSON AND LASCH, 1981; GAMSON AND MODIGLIANI, 1989). The results show a preponderance of the UF faculty as sources, in a framework that places these institutions as a place where the main agents capable of analyzing and explaining events are. Another very prominent framework is the tension between the political and scientific fields, mainly due to criticism between the fields regarding the epidemiological crisis caused by the covid-19.